Pengaruh Kualitas Laporan Keuangan, Lama Jabatan dan Rasio Pembiayaan Utang terhadap Transparansi Pemerintah Daerah melalui Website - Wijita Lutvitasari; Lintang Venusita (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study was conducted to determine whether there is an influence of the quality of financial reports, length of office and debt financing ratio on local government transparency through the website. The sampling technique used purposive sampling consisting of all local governments in Indonesia in 2023 with a sample size of 513 local governments. Based on the statistical tests that have been carried out, the results of this study indicate that the quality of financial reports and the size of the local government have an effect on local government transparency through the website. While the length of office does not affect local government transparency through the website.